Efektifitas Terapi Akupuntur Terhadap Penderita Hipertensi - Agnes Erida Wijayanti; Doni Setiyawan; Regina Widyaningtyas (STIKes Surya Global Yogyakarta, 2023)
Background of Study : Hypertension in elderly caused by many factors that were closely related with aging process. One of the non-pharmacological treatment methods is acupuncture therapy. The needle prick method in acupuncture will stimulate the release and activation of active substances such as Nitric Oxide (NO). Needle prick at the acupuncture will stimulate impulses parasympathetic nervous and pressed sympathetic nervous. The parasympathetic dominant will issue of acetylcholine, Where ties acetylcholine in endothelial cells to induce the formation of local nitrite oxide, Which are then diffuses passing through the smooth muscle blood vessels, and then affect blood flow and local, circulation so there. smooth muscle relaxation of the blood vessels. Research purposes determine the effect of acupuncture on hypertensive patients.Methods : This research was conducted in Klinik pakualaman II Omah Gandok Tajem Sleman. This research is a pre-experimental research design with One-Group Pretest-Posttest Design. The population in this study were patients with hypertension and the sample was taken by purposive sampling method. The data were processed and analyzed using paired t-test with a significance value of p0.05.Results : The results obtained that the value of p = 0.000 in the systole measurement and p = 0.007 in the diastolic measurement (p 0.05) means that there is a significant difference in the respondent's blood pressure before acupuncture is performed with blood pressure after acupuncture is performed.Conclusion : there is a difference in the decrease in blood pressure before and after being given acupuncture therapy